Exploring the changing association between parental and adolescent fruit and vegetable intakes, from age 10 to 30 years - Tanya Braune; Jean Adams; Eleanor M. Winpenny (BMC, 2024)
Abstract Background Adolescence is a pivotal developmental stage, where escalating rates of overweight and obesity have raised concerns about diet quality and its association with adverse health outcomes. Parents are known to have considerable influence on childhood diet, but how this influence changes as adolescents mature is unknown. This study investigates the association between parental fruit and vegetable (FV) intake and adolescent FV consumption, exploring how this changes across adolescence and when adolescents leave home. Methods Adolescents aged 10-30 years (n = 12,805) from the UK Household Longitudinal Study (UKHLS), and their parents, reported FV intakes every 2 years. Multilevel linear regression models were fitted to assess associations between parental and adolescent FV intakes, investigating interactions with age and living arrangement, and adjusting for sociodemographic covariates. Results Parental FV intake was positively associated with adolescent FV intake (β = 0.20 [95%CI:0.19,0.22] portions/day), with the strength of this association lowest during early adolescence (10-14 years) and peaking at 17-18 years (β = 0.30 [95%CI: 0.27,0.33] portions/day). When adolescents no longer lived in the parental home, the association of parental FV intake with adolescent FV consumption decreased, but a positive association was maintained up to age 30 years. Conclusions Our findings emphasise the enduring effect of parental FV consumption on adolescent FV consumption, highlighting the potential for interventions to promote increased FV intake, acknowledging the lasting influence of parental diet, even beyond the confines of the parental home.